2004
DOI: 10.1111/j.1365-2222.2004.02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mite‐impermeable mattress encasings and an educational package on the development of allergies in a multinational randomized, controlled birth‐cohort study – 24 months results of the Study of Prevention of Allergy in Children in Europe

Abstract: In this study, HDM avoidance did not show a protective effect on the development of sensitization to HDM or symptomatic allergy in children at age 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 27 publications
(52 reference statements)
2
56
0
2
Order By: Relevance
“…Children of families who had applied all three measures had less wheeze and asthma than children of families who executed only two measures. The studies might explain why avoidance of a single exposure has only marginal or no effects when other exposures are still existing, as might have been the case in other prevention studies [18,35]. In tertiary prevention of asthma intervention studies [46], focusing on a reduction of multiple environmental exposures has shown promising results, whereas the results of clinical trials targeting only one allergen were disappointing [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children of families who had applied all three measures had less wheeze and asthma than children of families who executed only two measures. The studies might explain why avoidance of a single exposure has only marginal or no effects when other exposures are still existing, as might have been the case in other prevention studies [18,35]. In tertiary prevention of asthma intervention studies [46], focusing on a reduction of multiple environmental exposures has shown promising results, whereas the results of clinical trials targeting only one allergen were disappointing [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Several randomised intervention studies have reported results on various clinical symptoms at age 1 [17,20,34], 2 [18,35], 3 [36], 4 [37] and 8 yrs [19]. When the results of intervention studies are compared, it has to be kept in mind that comparison is hampered, as the studies differ in defining high-risk cases, the applied intervention(s) and the definition of outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ongoing studies are investigating the effects of environmental control on the primary prevention of asthma and allergies. Although the results of a pan-European study (1833) of 4 y old children and the Isle of Wight (1834) and Canadian studies (1835) at ages 8 and 7 y provide some encouragement, the preventive effect of the avoidance of HDM allergen alone during pregnancy or after birth is disappointing (1836)(1837)(1838)(1839)(1840)(1841). It will therefore be some time before a definitive public health message emerges.…”
Section: Primary Prevention Of Atopic Diseasesmentioning
confidence: 99%
“…In total, 10 high-quality studies (enrolling 3473 patients) were included, of which 1124 had a multifaceted intervention design [23][24][25] and 2349 had a mono-intervention design. 21,[26][27][28][29][30][31] Several studies had repeated measurements on different ages of the children. The results suggested that a multifaceted approach might be effective in delaying or preventing asthma, whereas a mono-intervention does not seem to have such a protective effect.…”
Section: C) the Interaction Between Genotype And Environment -Childhomentioning
confidence: 99%